2004
DOI: 10.1088/0953-8984/16/32/009
|View full text |Cite
|
Sign up to set email alerts
|

Equations of state of GdFeO3and GdAlO3perovskites

Abstract: The structures of orthorhombic GdAlO3 and GdFeO3 perovskites have been refined at room temperature and pressure using single-crystal x-ray diffraction and their equations of state have been measured to pressures of 7.95 and 7.58 GPa, respectively. Both structures are distorted through the tilting and distortion of the octahedra. GdAlO3 isless distorted than GdFeO3 with an average Al–O–Al tilt angle of 156.42(16)° compared to an average Fe–O–Fe tilt angle of 147.10(10)° in GdFeO3. Both the FeO6 octahedra and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 28 publications
(36 reference statements)
6
22
0
Order By: Relevance
“…1.00; being βx = / ) is similar to that of other orthorhombic perovskites (b ≥ a ≥ c), like GdAlO3 (βa : βb: βc = 1.24 : 1.65 : 1.00) 12 , LaGaO3 (βa : βb: βc = 1.61 : 1.68 : 1.00) 13 , while the anisotropy in compression is smaller in the case of CaTiO3 (βa : βb: βc = 1.05 : 1.02 : 1.00) 46 and GdFeO3 (βa : βb: βc = 1.03 : 1.06 : 1.00) 12 GPa. 47 However, the experiments of Zhao et al suggested that the structure would likely to transform to a more distorted structure due to the differences in the compressibilities of the CaO12 and TiO6 polyhedral units.…”
Section: Resultssupporting
confidence: 74%
“…1.00; being βx = / ) is similar to that of other orthorhombic perovskites (b ≥ a ≥ c), like GdAlO3 (βa : βb: βc = 1.24 : 1.65 : 1.00) 12 , LaGaO3 (βa : βb: βc = 1.61 : 1.68 : 1.00) 13 , while the anisotropy in compression is smaller in the case of CaTiO3 (βa : βb: βc = 1.05 : 1.02 : 1.00) 46 and GdFeO3 (βa : βb: βc = 1.03 : 1.06 : 1.00) 12 GPa. 47 However, the experiments of Zhao et al suggested that the structure would likely to transform to a more distorted structure due to the differences in the compressibilities of the CaO12 and TiO6 polyhedral units.…”
Section: Resultssupporting
confidence: 74%
“…6. Interestingly, the large bulk modulus indicates NdCrO 3 is significantly less compressible than other simple perovskites such as LaCoO 3 150(2) GPa [28], CaZrO 3 154(1) GPa [29], CaSnO 3 163(1) GPa [30], SmNiO 3 167 GPa [31], CaTiO 3 171 GPa [32], SrTiO 3 174 GPa [33], PrAlO 3 176(9) GPa [34], GdFeO 3 182(1) GPa [35], LaAlO 3 190(5) GPa [36], GdAlO 3 191(1) GPa [35], YAlO 3 192(2) GPa [37], CaGeO 3 194(2) GPa [32], ScAlO 3 218(1) GPa [38], and NdFeO 3 244(4) GPa [39] and MgSiO 3 249 (3) GPa [40]. The relatively large uncertainty in the bulk modulus of NdCrO 3 , compared to the single crystal studies, stems from the limited number of volume data points and volume uncertainty caused by the pressure-induced peak broadening.…”
Section: Resultsmentioning
confidence: 99%
“…The volume variation of the more Nd-rich samples (x=0.12, 0.20, 0.62, 1.00) can be adequately fit with a Birch-Murnaghan third-order equation of state [39]. In common with other Pbnm perovskites [12,13], the pressure derivative of the bulk modulus, K 0 0 ¼ ðdK=dPÞ P¼0 , is in the range of 6-7. For the La-rich samples (x=0.00, 0.06) the phase transitions limit the pressure range over which the unit-cell data can be collected for the Pbnm phase, and the refinement of the third-order equation of state is not stable.…”
Section: Article In Pressmentioning
confidence: 87%
“…Recent single-crystal X-ray diffraction studies, along with previous research work, clearly indicate that the relative compressibilities of the A and B sites play an important role in determining the pressure-induced structural changes of perovskites [6][7][8][9][10][11][12][13][14][15][16][17]. When the BO 6 octahedra are less compressible than the extra-framework AO 12 sites the application of pressure leads to increased tilts of the octahedra within a single phase, or to phase transitions to perovskites with lower symmetries and larger tilts.…”
Section: Introductionmentioning
confidence: 99%